Genomic profiling of a six-generation patrilineal family of the Ming-Qing dynasties in China - Jincheng Wang; Tianming Zhang; Xiaowen Jia; Zihan Zhang; Jianing He; Chao Ning; Jihong Wang; Tingyu Yang; Guanbo Wang; Yuhong Pang; Yanyi Huang (iScience)
Summary: Family cemeteries from historical periods often follow structured burial patterns, but identifying these arrangements is challenging due to limited written records and ambiguities in archaeological interpretation. Archaeogenetics provides a precise means to determine biological kinship, enabling the reconstruction of social relationships and burial customs. Here, we analyzed ancient DNA and contextual data from 34 individuals at Qianweigou, a Ming-Qing dynasty cemetery in Beijing, reconstructing a six-generation patrilineal pedigree. The genomic data revealed strict patrilineal burial customs, with spouses jointly interred and a non-random west-to-east spatial arrangement reflecting generational chronology. Each generation occupied distinct positions, forming an echelon-like burial pattern. This study demonstrates how genetic data can clarify historical kinship organization, refining hypotheses about Ming-Qing burial customs and advancing our understanding of familial structures in late imperial China.